Memaknai Terjadinya Bencana Alam Merujuk pada Kajian Tafsir - Moh Rosyid (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2020)
The purpose of writing this text is to make Al-Quran a place to ask questions and remember the greatness of God. The closer humans are to God, humans always care for nature with full awareness. Messages of Al-Quran and newspaper coverage with methode tafsir bi ar-Ra’yi atau al-’aqli by qualitative descriptive analysis can be used as a life lesson. It is to realize that Divine power is second to none because He is the Almighty. Human negligence in caring for nature will cause disaster / natural disasters. Disasters are not always predictable by the sophistication of technology and science in terms of when to come and when the end of natural disasters due to human limitations. The Koran illustrates that natural disasters have occurred in humans since the beginning of time. The event has a variety of meanings to be used as material for life lessons.